Whole-blood PUFA and associations with markers of nutritional and health status in acutely malnourished children in Cambodia. Issue 6 (24th April 2020) - Sigh, Sanne; Lauritzen, Lotte; Wieringa, Frank T; Laillou, Arnaud; Chamnan, Chhoun; Angkeabos, Nheb; Moniboth, Duch; Berger, Jacques; Stark, Ken D; Roos, Nanna
Abstract: Objective: To measure fatty acid composition, particularly whole-blood PUFA content, in acutely malnourished children and identify associations with markers of nutritional and health status. Design: PUFA were assessed in dried blood spots obtained from a cross-sectional study. Nutritional and health status were assessed by anthropometry, haemoglobinopathies, inflammation and blood counts. Setting: Cambodia. Participants: The study was conducted with 174 children aged 0·5–18 years with acute malnutrition. Results: Among total fatty acids (FA), the relative percentage of total PUFA was 20 % FA, with 14 % of the children having very low PUFA (mead acid (MA):arachidonic acid (AA) >0·02, n -6 docosapentaenoic acid:DHA >0·2 and total n -6: n -3 PUFA >10·5). Wasting was not associated with any PUFA. Stunting and low height were consistently positively associated with total PUFA and positively with n -6 PUFA. Height was positively associated with n -3 long-chain PUFA (LCPUFA). The presence of haemoglobinopathies or inflammation was positively associated with MA:AA, but not total PUFA. Elevated blood platelet counts were positively correlated with linoleic acid and appeared to be influenced by anaemia ( P = 0·010) and inflammation ( P = 0·002). Monocyte counts were high during inflammation ( P = 0·052) and correlated positively with n -6 LCPUFA and n -3 LCPUFA. Conclusions: Children with acute malnutrition or stunting had low PUFA, while elevated platelets and monocytes were associated with high PUFA. In acutely malnourished children, inflammation could lead to elevated blood cell counts resulting in increased whole-blood PUFA which does not reflect dietary intake or nutritional status.